Correlation Between Maximal Eccentric and Isometric Multi-Joint Lower-Extremity Strength and Vertical Jumping Performance in Young Adults - Joonsun Park; Cassidy Weeks; Brennan J. Thompson; Talin Louder (Muscles)
Maximal eccentric (MES) and isometric (MIS) muscle strength may enhance vertical jump performance by facilitating preloading and reducing energy loss during the eccentric (ECC) phase of the stretch-shortening cycle (SSC). However, the contributions of ECC and isometric (ISO) strength to the countermovement (CMJ) and depth jump (DJ) remain unclear due to variability in assessment methods (e.g., dynamometry, isometric mid-thigh pull) and the limited range of metrics examined in prior research. The aim of this study was to assess correlations between multi-joint lower extremity MES and MIS, obtained using a seated multi-joint isokinetic dynamometer, and 13 vertical ground reaction force (GRF) measures derived from the performance of three maximal effort DJs and CMJs. Twenty-five healthy young adults participated in this study (age = 21.9 ± 2.9 years). Pearson r correlation coefficients were used to assess the statistical significance (α = 0.05) of the relationships between absolute (N) and body mass normalized (BN) maximal strength measures and vertical jumping metrics. Moderate-to-strong positive correlations were identified between MES and MIS with broad performance metrics in CMJ and DJ, including reactive strength index (r = 0.45–0.53, p < 0.05), modified reactive strength index (r = 0.41–0.62, p < 0.05), and jump height (r = 0.59–0.75, p < 0.05). Moderate-to-strong positive correlations were also observed between MES and MIS with CON work (r = 0.58–0.71, p < 0.05) and CON peak power (r = 0.44–0.71, p < 0.05) for both the CMJ and DJ. In contrast, moderate-to-strong negative correlations were observed between MES and MIS with ECC work (r = 0.42–0.62, p < 0.005) and ECC peak power (r = 0.45–0.60, p < 0.05). These findings suggest that enhanced neuromuscular efficiency and joint stiffness in stronger musculature reduce energy absorption during the eccentric phase, minimizing mechanical deformation and preserving elastic energy for concentric propulsion. Combined, MES and MIS optimize force application, energy utilization, and control, which are crucial for maximizing jump height. These findings underscore the role of MES and MIS in influencing jumping performance across both the ECC and CON phases of the SSC. This insight is valuable for practitioners designing training programs aimed at improving vertical jumping ability.